2016
DOI: 10.7748/nm.23.1.34.s29
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions and experiences of mentoring

Abstract: Pre-registration education programmes provide nursing students with the skills and knowledge to become safe and proficient practitioners. Assessment of students' competence is a fundamental part of these programmes and mentors play a crucial role. Mentors are registered nurses who have completed an appropriate mentorship programme in an approved higher education institution, and their main role includes teaching, supervising and assessing students' clinical competence. The role can be demanding and stressful, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…Regardless of type of mentoring relationship, the Phase III participants identified with mentors who modelled excellence in nursing care and strove to emulate their clinical practice habits. This finding agrees with that found by Douglas, Garrity, Shepherd, and Brown () in that the close mentoring interaction and the mentor's actions most positively influenced these participants’ socialization into the nursing profession. Furthermore, the positive close interactions may develop faster with an officially structured, formal mentor relationship compared to an informal one.…”
Section: Discussionsupporting
confidence: 91%
“…Regardless of type of mentoring relationship, the Phase III participants identified with mentors who modelled excellence in nursing care and strove to emulate their clinical practice habits. This finding agrees with that found by Douglas, Garrity, Shepherd, and Brown () in that the close mentoring interaction and the mentor's actions most positively influenced these participants’ socialization into the nursing profession. Furthermore, the positive close interactions may develop faster with an officially structured, formal mentor relationship compared to an informal one.…”
Section: Discussionsupporting
confidence: 91%
“…This study highlights the academic educators' and clinical preceptors' perceptions of their transition-to-practice program collaboration. Consistent with existing literature (Douglas et al, 2016;Kennedy & Chesser-Smyth, 2017), a lack of communication between clinical preceptors and academic educators was also reported in this study. To overcome this, previous studies suggested that the presence of academic educators in clinical settings is necessary to encourage better communication with clinical preceptors (Couper, 2015;Douglas et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Mentors may feel dissatisfaction when they have responsibilities for unmotivated or challenging students (O'Brien et al, 2014) and need more support from nurse teachers in these situations. Mentors also value their support when they face challenges in assessing students' competence for passing or failing students in clinical practice (Douglas, Garrity, Shepherd, & Brown, 2016). Continuous guidance and discussions through practice are essential for students, because it is easier to adopt practices according to one's levels of knowledge and skills (McSharry & Lathlean, 2017).…”
Section: Discussionmentioning
confidence: 99%